Surgical management of preauricular based on plastic-reconstructive algorithm - Dini Widiarni Widodo; Hemastia Manuhara Harba'i (PERHATI-KL, 2019)
Background: Preauricular fistula is a congenital malformation of the six auditory hillocks during the development of auricle, when an imperfect fusion of the first arch tuberculum to other tuberculums occurred and generated a tract. It is characterized by a nodule or a dent located adjacent to the external ear. An infection will create a swollen area in front of ear auricles with pain and suppuration. Fistula extirpation should be carried out after the acute infection subsides. Purpose: To evaluate surgery techniques with the lowest complication and recurrence rate. Case report: Reporting 4 surgical cases of prearicular fistula treated by Plastic-Reconstructive ENT Head and Neck surgery, among 26 cases of preauricular fistula diagnosed between 2015 to 2017 in Cipto Mangunkusumo General Hospital. Methods: Searching literature through Pubmed, Wiley, Proquest and Google Schoolar with keywords of “Preauricular fistula AND surgical treatment”. Further selection through clinical questions. Results: One journal presented a systematic review on the surgical outcome of preauricular sinus excision techniques. Reporting 4 cases treated by plastic-reconstructive surgery based on the systematic review above mentioned. Conclusion: The supra auricular approach could be recommended as a good technique for preauricular fistula, in particular for the infected and/or the recurrent cases. Latar belakang: Fistel preaurikula adalah suatu kelainan malformasi kongenital, dimana tuberkulum arkus brakialis pertama tidak menyatu dengan tuberkulum lainnya, sehingga terbentuk sebuah traktus (saluran). Fistel preaurikula ditandai oleh adanya nodul atau cekungan yang tampak di dekat telinga luar. Bila terjadi infeksi biasanya menyebabkan daerah di depan daun telinga bengkak dan nyeri, serta bernanah. Ekstirpasi fistel sebaiknya dilakukan setelah infeksi akut mereda. Tujuan: Mengevaluasi teknik bedah dengan tingkat komplikasi dan kekambuhan terendah. Laporan kasus: Dilaporkan 4 kasus fistel preaurikula yang ditatalaksana oleh bedah THT-KL plastik-rekonstruksi, dari sejumlah 26 kasus yang datang berobat di RSUPN Cipto Mangunkusumo, antara Januari 2015 dan April 2017. Metode: Penelitian literatur melalui Pubmed, Wiley, Proquest, dan Google Schoolar dengan kata kunci “Preauricular fistula AND surgery treatment”. Seleksi literatur lebih lanjut melalui pertanyaan klinis. Hasil: Didapati 1 jurnal yang menyajikan hasil operasi dari teknik bedah eksisi sinus preaurikular secara systematic review. Dilaporkan 4 kasus yang ditatalaksana dengan bedah plastik-rekonstruksi berdasarkan systematic review tersebut di atas. Kesimpulan: Pendekatan supra aurikula dapat direkomendasikan sebagai teknik bedah yang baik untuk penatalaksanaan fistel preaurikular, khususnya yang terinfeksi dan/atau berulang.